Why Infaq Remains Consumptive in Some Regions: A Comparative Study of Local Islamic Social Finance Practices - Isti Nuzulul Atiah; Sri Herianingrum; Fuad Hasyim; Najmudin Najmudin; Siti Sofiaturrohmah (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Islamic social finance is increasingly recognized as a strategic instrument for economic empowerment; however, infaq utilization remains predominantly consumptive in many institutional contexts. This study develops an institutional governance explanation for why infaq functions productively in some regions while remaining consumptive in others. Drawing on institutional governance theory and Islamic social finance literature, this study argues that the transformation of infaq depends on governance capability, policy coherence, and ecosystem integration rather than on the intrinsic characteristics of the instrument. Using a qualitative comparative design based on secondary data from four regions in Indonesia, this study examines variations in institutional capacity, governance structure, and program integration. The findings show that productive infaq utilization is closely associated with institutional capability configuration, including structured program design, policy alignment, and integration with microenterprise empowerment systems. This study introduces the Localized Productive Infaq Governance (LPIG) model, which explains how governance capability enables the transformation of philanthropic funds into productive social capital. This study contributes to Islamic social finance literature by advancing a governance-centered theoretical framework and offering a transferable institutional model applicable to diverse Islamic social finance ecosystems.